Lay Female Devotional "Lives" in the Counter Reformation - Hillman, Jennifer (Church history and religious culture, 2017)
In 1563, the Catholic Church responded to the Protestant challenge to the religious life as the most holy feminine state with the maxim aut maritus aut murus (wife or wall). The navigation of that dictum by early modern women across Catholic Europe has arguably been one of the dominant themes in the scholarship over the last thirty years. Certainly, there had always been the opportunity for women to lead a religious life outside of marriage and the cloister as beatas, tertiaries and beguines. Yet it was after the Council of Trent (1545–1563) that women had to renegotiate a space in the world in which they could lead spiritually-fulfilling devotional lives. If this was one unintended legacy of 1517, then the quincentenary of the Reformation seems a timely moment to reflect on new directions in the now burgeoning historiography on lay women in Counter-Reformation Europe.